Milk production and composition in Charolais and Angus cows nursing straightbred or crossbred calves - Ribeiro, Edson Luis de Azambuja; Restle, João; Pires, Cleber Cassol (Pesquisa Agropecuaria Brasileira, 1991)
The experiment evaluated the production and composition of milk produced by Angus (A) and Charolais (C) cows nursing straightbred (A and C) or F1 crossbred calves (NA = 1/2 Nelore - 1/2 Angus and NC = 1/2 Nelore - 1/2 Charolais). Charolais cows produced more (P < 0.01) milk than Angus cows (3.86 vs 3.17 l/day). Average daily milk production of cows nursing crossbred calves (3.83 l) was higher (P < 0.01) than of cows nursing straightbred calves (3.19 l). Average daily milk production of A cows nursing crossbred or straightbred calves was 3.35 and 2.99 l, respectively, while for the Charolais cows it was 4.31 and 3.4 l, respectively. Breed of cow affected (P < 0.05) only the percent solids-not-fat, which was 8.28 and 8.15%, respectively, for C and A cows. Milk composition was not affected (P < 0.05) by breed of calf. Sex of calf did not affect (P < 0.05) production or milk composition.